Sharia Leasing as an Alternative Financing: SLR of Islamic Economics and Sharia Law Literature - Moh. Sudirman; Taufiqur Rahman (Penerbit Hellow Pustaka, 2025)
Sharia leasing is an alternative financing based on sharia principles that is increasingly in demand as a substitute for conventional schemes. This instrument avoids usury, gharar, and maysir and emphasizes fair and transparent transactions in accordance with Islamic law. This study aims to conduct a systematic literature review (Systematic Literature Review/SLR) to identify basic concepts, views of muamalah fiqh, operational challenges, and prospects for its development in Indonesia. The method used is SLR with sources from databases such as Google Scholar, ScienceDirect, Scopus, and the Garuda Portal of the Ministry of Education and Culture for the 2018–2025 period. The literature was analyzed using a thematic approach to obtain a comprehensive picture. The results of the study indicate that sharia leasing has a strong basis in muamalah fiqh through contracts such as ijarah and its combinations. However, its implementation still faces challenges such as lack of harmonization of contracts, low public literacy, and the need to improve national regulations. As a solution, contract standardization, digitalization of sharia services, public education, and synergy between regulators, business actors, and academics are needed. The MSME and transportation sectors are strategic segments with increasing demand. The conclusion of the study states that sharia leasing has great potential as a modern Islamic economic instrument, as long as it is supported by strong policies and sustainable technological innovation.